2002
DOI: 10.1182/blood-2002-04-1115
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 21 prevents antigen-induced IgE production by inhibiting germ line Cε transcription of IL-4–stimulated B cells

Abstract: Interleukin 21 (IL-21) has recently been identified as a multifunctional cytokine that induces the proliferation of T cells and B cells and differentiation of natural killer cells. To determine whether IL-21 regulates IL-4–mediated immune responses, we examined the effect of IL-21 on antigen-specific IgE production in mice. We also examined the effect of IL-21 on IL-4–induced IgE production from B cells and antigen-induced T-helper 2 (Th2) cell differentiation. The in vivo injection of IL-21 prevented antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
188
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 43 publications
13
188
2
1
Order By: Relevance
“…By the addition of anti-IL-12 or anti-IFN-γ antibody, it was suggested that MN45-induced IL-12 led to IFN-γ induction and that the IFN-γ was involved in the suppression of IgE production without suppressing IL-4 production. It has been reported that IFN-γ not only suppresses IL-4 production by Th2 cells but also regulates IgE class switch recombination in B cells or enhances production of IL-21, which suppresses the synthesis of IgE (Obayashi et al, 2007;Pène et al, 2006;Suto et al, 2002). We suppose that MN45 induces IFN-γ through IL-12 production, 12 production significantly (Fig.…”
Section: Figmentioning
confidence: 98%
“…By the addition of anti-IL-12 or anti-IFN-γ antibody, it was suggested that MN45-induced IL-12 led to IFN-γ induction and that the IFN-γ was involved in the suppression of IgE production without suppressing IL-4 production. It has been reported that IFN-γ not only suppresses IL-4 production by Th2 cells but also regulates IgE class switch recombination in B cells or enhances production of IL-21, which suppresses the synthesis of IgE (Obayashi et al, 2007;Pène et al, 2006;Suto et al, 2002). We suppose that MN45 induces IFN-γ through IL-12 production, 12 production significantly (Fig.…”
Section: Figmentioning
confidence: 98%
“…Total cellular RNA was prepared, and RT-PCR analysis was performed as previously described (24). In brief, Flag-IL-25R-expressing WT MEF or TRAF6 Ϫ/Ϫ MEF were stimulated with anti-Flag mAb (2 g/ml) at 37°C for 3 h and the total cellular RNA was isolated using Isogen solution (Nippon Gene) according to the manufacturer's instruction.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Whether IL-21 regulates IL-4-induced Th2 cell differentiation directly (32,33) or amplifies Th2-driven responses by downregulating the expansion of IFN-g-producing Th1 cells (33,34) remains incompletely understood. Under Th2 polarizing conditions in vitro a significant number of IL-21 + cells coexpress IL-4 (35), and a deficiency in the IL-21R is associated with decreases in both serum IL-4 and IL-4R expression on macrophages following infection (31) and in allergic responses (36).…”
mentioning
confidence: 99%